2019
DOI: 10.9758/cpn.2019.17.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Pentoxifylline on Learning and Memory Impairment Induced by Hypoxic-ischemic Brain Injury in Rats

Abstract: Objective Hypoxic-ischemic (HI) brain injury in the human perinatal period often leads to significant long-term neurobehavioral dysfunction in the cognitive and sensory-motor domains. Using a neonatal HI injury model (unilateral carotid ligation followed by hypoxia) in postnatal day seven rats, the present study investigated the long-term effects of HI and potential behavioral protective effect of pentoxifylline. Methods Seven-day-old rats underwent right carotid ligati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 87 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…According to previous studies, the appropriate dose of pentoxifylline 100 mg / kg was chosen. (Neves et al 2015;Halis et al 2019). In previous studies, the dose of rolipram in combination with another phosphodiesterase inhibitor was halved.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, the appropriate dose of pentoxifylline 100 mg / kg was chosen. (Neves et al 2015;Halis et al 2019). In previous studies, the dose of rolipram in combination with another phosphodiesterase inhibitor was halved.…”
Section: Methodsmentioning
confidence: 99%
“…As increased number of people transport to high altitudes for all reasons in recent years, the effects of altitude environmental exposure on L&M cannot be ignored, and finding strategies to relief or even prevent high altitude-induced CNS disorders is thus of worthy. On the one hand, studies have found that pentoxifylline (PTX), hydrogen, and ginkgolide B can improve L&M by relieving the apoptotic damage of hippocampal neurons [ 103 , 109 , 145 ]. Salidroside analogs could improve the body's oxygen utilization and the total oxyradical scavenging capacity (TOSC) to protect brain function without significant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Both IL-1 and TNF- α receptor antagonists can attenuate the effect above. The use of pentoxifylline can significantly reduce caspase-3 activity and lighten apoptosis caused by hypoxia [ 103 ]. In addition, different regions bear different oxidative stress responses.…”
Section: Impaired Landm Caused By Hypoxia Environment At High Altitudementioning
confidence: 99%
“…We selected the doses of rolipram and pentoxifylline according to the literature, and in the case of rolipram, a lower dose was chosen due to the side effects of this drug. [ 30,31 ] Evidence showed that the dose of rolipram was halved when combined with another phosphodiesterase inhibitor. Therefore, the first we chose rolipram dose and then adjusted pentoxifylline similar dose.…”
Section: Methodsmentioning
confidence: 99%